PRINSIP-PRINSIP EKONOMI SYARIAH DAN PENGAWASAN SYARIAH - Santi, Mei (LIPI, 2017)
The principles of sharia economy are: First, Islamic economy is nothing but an economic form to create a quality life. Second, not exploitative (usury). Third, the prohibition of gambling and speculation. Fourth, Islamic economics is the Welfarist economy. Fifth, maintain spiritualism in the public sphere. In the sharia economy has its own rules for economic activities remain in the principles of sharia. Therefore, in the implementation of Islamic economic supervision, there are the role of the ulama, the Sharia Supervisory Board, the National Sharia Board and the Financial Services Authority.